Mental health nurses' contributions to community mental health care: An Australian study - Heslop, B.; Wynaden, Dianne; Tohotoa, Jenny; Heslop, Karen (Wiley-Blackwell Publishing Asia, 2016)
Australian mental health policy is focused on providing mental health care in the community setting and community mental health teams provide services to clients in a shared model with primary care. The historical literature reports that community mental health nurses’ experience high levels of stress and are often allocated the most complex and challenging clients managed by the team. Yet information on their specific roles remains limited. This paper reports on research conducted at one Australian public mental health service to identify the components of the community mental health nursing role and to quantify the time nurses spent in each component during the study period. Six focus groups were conducted with community mental health nurses to identify their perceived role within the team. Data analysis identified 18 components of which 10 were related to direct clinical contact with clients and eight covered administrative and care coordination activities. A data collection tool based on the findings of the focus groups was designed and nurses recorded workload data on the tool in 15-min intervals over a 4-week period. Seventeen nurses collected 1528 hours of data. Internal coordination of care was identified as the top workload item followed by clinical documentation and national data collection responsibilities supporting the complexity of the community mental health nursing role. The high rating attached to the internal coordination of care role demonstrates an important contribution that community mental health nurses make to the functioning of the team and the delivery of quality mental health care.